2023
DOI: 10.3390/nano13142100
|View full text |Cite
|
Sign up to set email alerts
|

Cs2TiI6 (Cs2TiIxBr6-x) Halide Perovskite Solar Cell and Its Point Defect Analysis

Abstract: This work presents a comprehensive numerical study for designing a lead-free, all-inorganic, and high-performance solar cell based on Cs2TiI6 halide perovskite with all-inorganic carrier transport layers. A rigorous ab initio density-functional theory (DFT) calculation is performed to identify the electronic and optical properties of Cs2TiI6 and, upon extraction of the existing experimental data of the material, the cell is designed and optimized to the degree of practical feasibility. Consequently, a theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The EVBM, ECBM, and band gap data for PVK were obtained from our previous works 33 and FTO. 56 The energy band alignment diagram presented in this study illustrates a significant improvement in the performance of PSCs through the incorporation of an SSSO as both a passivating layer at the interface and a UV filter. The conduction band energy level (ECB) in the FTO/SnO 2 −SSSO film aligns more compatibly with the energy level of the PVK layer compared to the ECB in the pure FTO/SnO 2 film.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The EVBM, ECBM, and band gap data for PVK were obtained from our previous works 33 and FTO. 56 The energy band alignment diagram presented in this study illustrates a significant improvement in the performance of PSCs through the incorporation of an SSSO as both a passivating layer at the interface and a UV filter. The conduction band energy level (ECB) in the FTO/SnO 2 −SSSO film aligns more compatibly with the energy level of the PVK layer compared to the ECB in the pure FTO/SnO 2 film.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…In Figure f, we displayed an energy band alignment diagram for the devices being studied. The EVBM, ECBM, and band gap data for PVK were obtained from our previous works and FTO . The energy band alignment diagram presented in this study illustrates a significant improvement in the performance of PSCs through the incorporation of an SSSO as both a passivating layer at the interface and a UV filter.…”
Section: Resultsmentioning
confidence: 99%
“…The band structure and optical absorption results demonstrated that all A 2 Sn 1−x Ti x Br 6 (A = K, Rb, Cs) materials are semiconductors with band gaps between 0.9-1.6 eV, and A 2 TiBr 6 (A = K, Rb, Cs) compounds have the highest optical absorption both in the visible and ultraviolet regions, making them excellent materials for photovoltaic applications. Urmi et al computed the opto-electronic properties of Cs 2 TiI 6 (Cs 2 TiI x Br 6-x ) halide perovskite and the findings showed that this material has a considerable potential as a low-band gap alternative material for photovoltaic applications [28]. In this work, the cluster expansion (CE) method based on a genetic algorithm was used to predict new structures of Br-doped CsPbI 3 and to further predict their structural, electronic, optical, mechanical, and thermodynamic properties using the first-principle calculations.…”
Section: Introductionmentioning
confidence: 99%